Yeasts and wine acidity profile - Ana-Marija Jagatić Korenika; Luka Marinov; Dominik Anđelini; Ana Jeromel (Journal of Central European Agriculture, 2020)
Wine contains a large number of different chemical compounds, the interaction of which influences the formation of its quality defined by the intensity and quality of the color, its aromatic and taste properties. It is the presence of organic acids and their interrelationship that plays a significant role in the formation of taste quality whereby those with lower concentrations of certain acids will be palatably empty and dull, potentially more exposed to microbial contamination, while those with excessive acidity will taste rough and unbalanced. Tartaric, malic and citric acids are the main organic acids in grapes and wine and at the same time play the most important role in the formation of an acidity profile. However, during alcoholic fermentation, other organic acids such as succinic, pyruvic, lactic and acetic acids can also be produced by the yeasts and/or bacteria activity, thereby directly affecting the acidity profile of the wine. The contribution of Saccharomyces yeast to the change in the concentrations of individual organic acids is significantly lower compared to non-Saccharomyces species and is mainly related to the synthesis of succinic acid. In the past non-Saccharomyces species were treated exclusively as spoilage yeasts but nowadays it is somewhat different, with particular attention being paid to exploring their ability to modify the acidic profile of wine by increasing and/or reducing the synthesis of lactic, succinic, malic and pyruvic acid.